Online Self‐Administered Training of PTSD Treatment Providers in Cognitive–Behavioral Intervention Skills: Results of a Randomized Controlled Trial. Issue 6 (18th December 2014) - Ruzek, Josef I.; Rosen, Raymond C.; Garvert, Donn W.; Smith, Lauren D.; Sears, Katharine C.; Marceau, Lisa; Harty, Brian; Stoddard, Anne M.
Abstract : Despite potential advantages in scalability and efficiency of web‐based training for trauma providers, few controlled trials of feasibility and effectiveness of web‐based mental health training have been performed. Our study compared web‐based training in 3 intervention skills (motivation enhancement [ME], goal setting [GS], behavioral task assignment [BTA]) with web‐based training plus telephone consultation, and a no‐training control. The primary outcome measures included objective measures of skills acquisition (standardized patient assessments). Results showed significant differences among the training conditions. The overall tests of differences among the groups were statistically significant for ME and BTA skills ( p < .001 and p = .005, respectively), but not for GS ( p = .245). The web training plus consultation group improved in ME skills by 0.35 units compared to 0.12 units in the web only group ( p < .001) and no change in the control group ( p = .001). For BTA skills, the web training plus consultation improved by 0.27 units compared to 0.17 units in the web only group ( p = .175) and no change in the control group ( p = .004). Overall, these findings support the use of web‐based dissemination for large‐scale training programs for trauma providers in health care delivery systems. Further studies are needed to clarify the specific role of consultation as an adjunct to web‐based training.